Potential bio-control of patulin producing Penicillium expansum in post-harvest fruits using antagonistic yeasts - Coelho, A. R.; Levy, R. M.; Hoffmann, F. L. [UNESP]; Taniwaki, M. H.; Kmelmmeier, C.; Pagnocca, F. C. [UNESP]; Hirooka, E. Y. (Brill Academic Publishers, 2023)
The use of innocuous yeasts as bio-control agents to prevent Penicillium expansum contamination of apples and subsequent production of patulin can enhance refrigerated storage and has less environmental impact than conventional fungicides. The antagonistic potential of yeasts of natural origin against a toxigenic P. expansum strain was evaluated. In a preliminary assessment, Pichia membranifaciens E.C. Hansen and Sporobolomyces roseus Kluyver & van Niel, showed antagonistic/biodegradation properties which decreased patulin in broth from 5.9 mg/l to 2.9 mg/l. Further investigations were performed with 17 yeast isolates from various sources including maize silage, papaya, and grape fruit. Debaryomyces hansenii var. hansenii strain C1 from maize silage showed nutrient competition antagonism in its inhibition of the growth of P. expansum strain #2 on solid media after 120 hr incubation at 21 °C, while D. hansenii strain C7 displayed a antibiosis/parasitism pattern of antagonism. In nutrient broth P. ohmeri and C. guilliermondii P3. P. ohmeri inhibited conidia germination and mycelial growth the most after 12 hours at 21 °C. The data indicates a potential application of these yeasts in post-harvest control of spoilage/mycotoxigenic fungi in fruits.
Keywords: Antagonism; Fruits; P. expansum; Patulin; Yeast